Acetaminophen pharmacokinetics in infants and children with congenital heart disease. Issue 1 (7th November 2022) - Holladay, Jay; Winch, Peter; Morse, James; Anderson, Brian J.; McKee, Christopher T.; Rice‐Weimer, Julie; Tobias, Joseph D.
Abstract: Background: Acetaminophen is routinely used for perioperative analgesia in children undergoing major surgical procedures. There are few estimates of acetaminophen pharmacokinetic parameters in children with congenital heart disease, especially those with cyanotic heart disease. Aims: The current study prospectively investigated differences in acetaminophen pharmacokinetics following surgery using cardiopulmonary bypass in children with cyanotic and acyanotic congenital heart disease. Methods: Children (2–6 years, 9–23 kg) presenting for median sternotomy for Fontan palliation (cyanotic patients) or two ventricle surgical repair (acyanotic patients) were eligible for inclusion. A single intravenous dose of acetaminophen (15 mg/kg) was administered at the start of sternal closure after separation from cardiopulmonary bypass. The time‐course of acetaminophen concentrations were described using non‐linear mixed effects models. One and two‐compartment disposition models with first‐order elimination were tested. Pharmacokinetic parameter estimates were scaled using allometry and standardized to a 70 kg person. Results: There were 208 acetaminophen concentrations assayed from 30 children, 15 with cyanotic, and 15 with acyanotic heart disease. A 2‐compartment model best described acetaminophen PK. Parameter estimates (population parameter variability, PPV%; 95% confidence interval, CI) were clearance CL 15.3 L.h‐1.70 kg‐1 (22.2%; 13.8–16.7), intercompartment clearance Q 45.4 L.h‐1.70 kg‐1 (22.4%; 25.2–61.9), central volume of distribution V1 33.5 L.70 kg‐1 (23.2%; 25.9–38.8), peripheral volume of distribution V2 32.1 L.70 kg −1 (21.7%; 25.9–38.8). Neither clearance nor volume parameters differed between cyanotic and acyanotic patients. Conclusions: Acetaminophen pharmacokinetics were characterized using a 2‐compartment model with first‐order elimination following cardiac bypass surgery in children. Population pharmacokinetic parameter estimates were similar to other studies in children. No differences were detected between patients with cyanotic and acyanotic heart disease.